Repetition of Pesudo-Words in specific language disorder - Pérez Herráiz, Cristina; Moraleda Sepúlveda, Esther (Revista de Investigación en Logopedia, 2021)
Numerous explanatory hypotheses support the existence of limitations in the phonological loop of people with Specific Language Disorder. The repetition of pseudo-words is a task sensitive to the capacity of the phonological loop within the Working Memory, since this repetition causes the child to temporarily maintain phonological information, to later reproduce it. The main objective of this work is to provide new information about the differences in outcomes between typically developing children with language disorders when faced with a pseudo-word repetition task where the stimuli have been strictly controlled at the phonological level. A total of 36 children between 7 and 12 years old participated in this study: 18 children with typical development and 18 with previous diagnosis of TEL. To carry out this study, a pseudo-word repetition test was developed, controlling for variables such as length, frequency, composition, accentuation, and repetitions of each syllable. The results obtained show that children with TEL are more sensitive to the variables of length, frequency, and the interaction between them. Similarly, data have shown that the position in which an infrequent syllable appears plays an important role, causing greater errors in children with TD when the infrequent syllable is in the last position. The data obtained show the need to continue systematically analyzing the interaction between the length and frequency variables. In addition, the implications for clinical diagnosis are discussed.
Keywords: Specific language disorder; pseudo-words; working memory; phonological loop